Utilization of the @pusdiklatanri Instagram Account as a Medium for Archival Information and Education - Prasetya, Rafli Dwi; Wijaya, Abung Supama (The International Journal of Politics and Sociology Research, 2025)
Digital transformation has pushed social media to become a strategic space for government institutions to convey information. PPSDM ANRI utilizes Instagram @pusdiklatanri to reach the public and educate about archives through visual and interactive content. This research is interestingly studied using Media Richness Theory which highlights the immediacy feedback, multiple cues, language variety, and personal focus. The method used is qualitative through observation, interviews with social media team, and literature study. This research aims to analyze how the @pusdiklatanri Instagram account is utilized to deliver archival information and education. It focuses on how strategically the account serves as a digital communication medium for PPSDM ANRI to reach the public. The results show that @pusdiklatanri functions not only as a formal information platform, but also as a dynamic interaction and education space. This success is reflected in the multimodal content, language variety, and emotional closeness through videos, stories, and Q&A. This confirms the effectiveness of strategically managed social media. In conclusion, @pusdiklatanri is able to fulfill the characteristics of rich media in Media Richness Theory. Future research is recommended to compare similar accounts in other institutions or add quantitative analysis related to audience engagement.